Evolving concepts of assessment in a competency-based world. (3rd June 2017) - Harris, Peter; Bhanji, Farhan; Topps, Maureen; Ross, Shelley; Lieberman, Steven; Frank, Jason R.; Snell, Linda; Sherbino, Jonathan; ,
Abstract: Competency-based medical education (CBME) is an approach to the design of educational systems or curricula that focuses on graduate abilities or competencies. It has been adopted in many jurisdictions, and in recent years an explosion of publications has examined its implementation and provided a critique of the approach. Assessment in a CBME context is often based on observations or judgments about an individual's level of expertise; it emphasizes frequent, direct observation of performance along with constructive and timely feedback to ensure that learners, including clinicians, have the expertise they need to perform entrusted tasks. This paper explores recent developments since the publication in 2010 of Holmboe and colleagues' description of CBME assessment. Seven themes regarding assessment that arose at the second invitational summit on CBME, held in 2013, are described: competency frameworks, the reconceptualization of validity, qualitative methods, milestones, feedback, assessment processes, and assessment across the medical education continuum. Medical educators interested in CBME, or assessment more generally, should consider the implications for their practice of the review of these emerging concepts.